Analisis Peran Artificial Intelligence dalam Proses Evaluasi Pembelajaran Bahasa Indonesia di Kalangan Mahasiswa; Studi Kasus di Sekolah Tinggi Ilmu Ekonomi Balikpapan - Aisyah, Aisyah; Ryndu, Aisyah Bunga; Azahrah, Anissya; Puter, Sherin Auliya; Febriani, Widya; Anhar, Anhar (Indo-MathEdu Intellectuals Journal, 2025)
The development of artificial intelligence (AI) technology has brought significant changes to the digitization of education, including in higher education. This study aims to analyze the role of AI in improving the efficiency, accuracy, and personalization of learning evaluation in Indonesian language courses at the Balikpapan College of Economics (STIE). This study uses a qualitative approach with a single instrumental case study design, supplemented by participatory observation and analysis of survey data collected through Google Forms from STIE Balikpapan students. The results of the study show that the use of AI can accelerate access to information, tailor learning materials to individual needs, and improve the objectivity of evaluation. However, challenges related to ethical aspects and the potential misuse of AI in an academic context were also found. Therefore, clear regulations and adequate digital literacy are needed for both students and lecturers. These findings emphasize the importance of integrating adaptive and ethical AI in Indonesian language learning evaluations, without neglecting the humanistic values that form the foundation of education.